Pengaruh Pendidikan Nilai Kejujuran dan Self-Awareness terhadap Perilaku Anti-Kecurangan Akademik Siswa Kelas XI di SMK Negeri 1 Kasihan Bantul - Fathullah Gz; Ade Junaidi Rahmat; Saifuddin; Muhammad Alfi Syahrin (Education Research Center, 2026)
The study aims to analyze the influence of Education Value Honesty and Self-Awareness on Anti-Academic Cheating Behavior in XI SMK State 1 Kasihan Bantul. Research uses quantitative approaches with correlational-explanatory research types. The research sample totaled 20 students selected using simple random sampling techniques. Data is collected through a closed covered censet based on the Likert scale that has been tested for its validity and reliability. Data analysis is performed using descriptive statistics, classic assumption test, simple regression, and multiple linear regression. The results of the study showed that Honesty Value Education had a positive and significant effect on Academic Anti-Cheating Behavior with a determination coefficient value (R²) of 0.738 or 73.8%. Self-Awareness also has a positive and significant effect with a determination coefficient value (R²) of 0.783 or 78.3%. Simultaneously, Education Value Honesty and Self-Awareness has a significant effect on Academic Anti-Cheating Behavior with a determination coefficient value (R²) of 0.810 or 81.0%. However, on multiple regression analysis, only Self-Awareness exhibits partially significant influence. These findings suggest that self-awareness has a more dominant role in shaping academic anti-cheating behaviors. Therefore, academic fraud prevention efforts need to be done through strengthening education of honesty value integrated with the development of students’ self-awareness to build a sustainable culture of academic integrity